Evaluasi Usability Pada Antarmuka Pengguna Aplikasi PLN Mobile Menggunakan Metode Evaluasi Heuristik - Putri Ayu Lestari; Ismiarta Aknuranda; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PLN Mobile is a Mobile application built by PT. PLN which aims to provide electricity services through Mobile apps. PLN Mobile has several services, namely information, check bills, provision of electricity, complaints, and contact centers. The PLN Mobile application has not been able to achieve the objectives in providing convenience in Mobile services due to the many user complaints on user review playstore for navigation or difficult application usage, therefore it is necessary to do usability evaluation to find out usability problems that exist at the PLN Mobile application interface. In this study usability evaluation uses the Nielsen's heuristic method. Heuristic evaluation method is a method used to find usability problems in the interface design of a product based on 10 usability principles. Heuristic evaluation in this study was carried out by 4 expert usability. The heuristic evaluation of the PLN Mobile application found that there are 22 problem with the highest average severity rating found on the principle of H-3 (User control and freedom), namely the severity rating of 2.7. While the heuristic principle with the largest percentage of findings is H-4 (Consistency and Standards) with a percentage of 22,88% of all findings of the problem. This research also provides improvement recommendations from evaluators which are very useful to be used as a consideration for PLN Mobile to improve the application.